2020
DOI: 10.1039/d0ee01389g
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of crystal structure–stability correlation in iridates for oxygen evolution electrocatalysis in acid

Abstract: We provide general descriptions regarding the structure–stability correlations of iridium-based complex-oxide catalysts for oxygen evolution reaction in acid media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(146 citation statements)
references
References 55 publications
2
140
0
Order By: Relevance
“…Besides, the links between these two parameters (especially the stability in acidic environment) and some other factors, such as conductivity, thermodynamics, dissolution rate, or even the structure have been studied. [87,95,126,147,230] For example, Markovic's group obtained the inverse activity-stability trends in the OER process under acidic condition. [126] The same authors then reported nanoporous Ir/IrO 2 through de-alloying of Os from an Ir 25 Os 75 alloy with well-balanced activity and stability.…”
Section: Balancing the Relationship Of Stability With Other Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the links between these two parameters (especially the stability in acidic environment) and some other factors, such as conductivity, thermodynamics, dissolution rate, or even the structure have been studied. [87,95,126,147,230] For example, Markovic's group obtained the inverse activity-stability trends in the OER process under acidic condition. [126] The same authors then reported nanoporous Ir/IrO 2 through de-alloying of Os from an Ir 25 Os 75 alloy with well-balanced activity and stability.…”
Section: Balancing the Relationship Of Stability With Other Factorsmentioning
confidence: 99%
“…They discovered the crystal structure-stability correlation in these iridates. [230] Compared with iridates, which have weak corner-sharing [IrO 6 ] connectivity, the ones with strong edge-or face-sharing [IrO 6 ] configuration can exhibit better structural stability, thus indicating the importance of crystal chemistry to precast stable catalysts.…”
Section: Balancing the Relationship Of Stability With Other Factorsmentioning
confidence: 99%
“…Ruthenates and iridates have exciting potential in various catalytic applications (Figure 1(c)), in part due to their resilience to extreme pH environments, and descriptions of their catalytic structure-property relationships that are centred on the geometry of (Ir/Ru)O 6 octahedra are highly analogous to those used in studies of quantum magnetism. [31][32][33] Ruthenates and iridates are also receiving considerable attention in the battery materials community (Figure 1(d)), with the consequence that contemporary materials discovery and development is progressing along a strikingly similar path to that in the quantum materials field, for example through the use of soft-chemical and electrochemical methods to access and manipulate lithium-, sodium-and hydrogen-containing materials. 10,[34][35][36] In fact, the exact same materials are often under study by the two communities at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…10 and Supplementary Table 1 . As all the thin-film samples were fabricated in an identical manner, the double-layer (DL) capacitance representing the electrochemically active surface area 9 , 45 , 46 does not vary between the samples regardless of the doping species (see Supplementary Fig. 11 and Supplementary Table 1 for the DL capacitance values).…”
Section: Resultsmentioning
confidence: 99%